Organic-Inorganic Hybrid Materials Based on Mesoporous Silica MCM-41 with b-Cyclodextrin and its Applications - M. Alahmadi, Sana; Mohamad, Sharifah; Jamil Maah, Mohd (Asian Journal of Chemistry, 2014)
This study explained the covalent attachment of b-cyclodextrin on MCM-41 through two different methods. In both methods, a diisocyanate was used as a linker. The modified mesoporous silicates characterized by Fourier transform infrared spectroscopy, thermal analysis and elemental analysis. The FTIR spectra and TGA analysis verified that the b-cyclodextrin was covalently attached to the mesoporous silica while the preservation of the MCM-41 channel system was checked by X-ray diffraction and nitrogen adsorption analysis. These materials were then used to evaluate the sorption properties of some organotin compounds (tributyltin, triphenyltin and dibutyltin). The results showed that mesoporous silica MCM-41 functionalized with b-cyclodextrins, using toluene di-iso-cyanate as a linker (MCM-TDI-b-CD), is a more highly effective sorbent for organotins especially for triphenyltin, compared to mesoporous silica MCM-41 functionalized with b-cyclodextrins using 3-chloropropyltriethoxysilane and toluene di-iso-cyanate as linkers (MCM-PTS-TDI-b-CD).